In-situ biogas upgrading assisted by bioaugmentation with hydrogenotrophic methanogens during mesophilic and thermophilic co-digestion. (March 2022) - Palù, Matteo; Peprah, Maria; Tsapekos, Panagiotis; Kougias, Panagiotis; Campanaro, Stefano; Angelidaki, Irini; Treu, Laura
Graphical abstract: Highlights: Bioaugmentation was carried out during in-situ biogas upgrading processes. Hydrogenotrophic methanogens were augmented in mesophilic and thermophilic reactors. Higher and durable CH4 production rate (+11%) was achieved at 37 °C. H2 accumulation hampered thermophilic biomethanation due to community perturbation. Long-term recovery of community function ultimately favored acetoclastic pathways. Abstract: In this study, the effects of bioaugmentation of typically dominant hydrogenotrophic methanogens to CSTR co-digesting cheese whey and manure, under in-situ biomethanation operations were investigated. Reactors working at mesophilic (37 °C) and thermophilic (55 °C) conditions were independently treated and examined in terms of microbial composition and process dynamics. Addition of Methanoculleus bourgensis in the mesophilic reactor led to a stable biomethanation, and an improved microbial metabolism, resulting in 11% increase in CH4 production rate. 16S rRNA and biochemical analyses revealed an enrichment in syntrophic and acidogenic species abundance. Moreover, nearly total volatile fatty acids conversion was observed. Differently, Methanothermobacter thermautotrophicus addition in the thermophilic reactor did not promote biogas upgrading performance due to incomplete H2 conversion and inefficient community adaptation to H2 excess, ultimately favoring acetoclastic methanogenesis. Bioaugmentation constitutes a viable tool to strengthen in-situ upgrading processes and paves the way to the development of more sophisticated and robust microbial inoculants.